A revision of Altman z-score model in financial distress prediction of listed companies in Vietnam - Tran, Duc Anh (2021)
The primary purpose of this report is to evaluate and improve the accuracy of Altman's Z-score model in financial distress prediction of listed companies in Vietnam. Identifying new cut off scores to the prediction models is necessary to adapt to the characteristics of the Vietnamese market. The study implements multiple discriminant analysis as a crucial methodology to calibrate the Z-score model with 51 forced delisted companies and 51 non-delisted companies. The Z new model achieves a one-year accuracy rate of 91.58% in forecasting financial distress for Vietnamese companies. The study shows that the superiority of the Altman Z-score model in financial distress prediction is not in the Z-score but in the methodology in which the model is built and put into practice.